2015
DOI: 10.4236/ojog.2015.510076
|View full text |Cite
|
Sign up to set email alerts
|

Can Waist Circumference Be Used as an Anthropometric Parameter to Assess the Obesity Related Pregnancy Outcome: A Case Control Study

Abstract: Introduction: The prevalence of obesity is increasing in women of reproductive age. Maternal obesity is associated with increased morbidity and mortality for both mother and offspring. BMI has been criticized as a limited measure of total obesity. Measurement of waist circumference can be useful in the assessment of abdominal obesity and disease risk. The study is aimed to evaluate the waist circumference as an anthropometric parameter in identifying women at risk of developing obstetric complications. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Logistic regression analysis revealed that the waist circumference was the only significant univariate predictor of preeclampsia (Z=2.04, P=0.04). The case control study by Anjali Gupta et al 15 PGIMS, Rohtak 2015 was aimed to evaluate the waist circumference as an anthropometric parameter in identifying women at risk of developing obstetric complications. The maternal and neonatal complications like preeclampsia (p = 0.0052, RR 0.5062, 95% CI 0.2935 -0.8728), gestational diabetes mellitus, preterm labor, postdatism, need for induction of labor (p value 0.0081, RR 0.6263, 95% CI 0.4314, 0.9091), instrumental vaginal delivery, cesarean delivery (p = 0.0072, RR 0.5745, 95% CI 0.3696, 0.8929), shoulder dystocia, PPH, macrosomia, neonatal asphyxia, admission to NICU were reported more in Group II women (waist circumference>80 cms) as compared to Group I (waist circumference<80 cms).…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis revealed that the waist circumference was the only significant univariate predictor of preeclampsia (Z=2.04, P=0.04). The case control study by Anjali Gupta et al 15 PGIMS, Rohtak 2015 was aimed to evaluate the waist circumference as an anthropometric parameter in identifying women at risk of developing obstetric complications. The maternal and neonatal complications like preeclampsia (p = 0.0052, RR 0.5062, 95% CI 0.2935 -0.8728), gestational diabetes mellitus, preterm labor, postdatism, need for induction of labor (p value 0.0081, RR 0.6263, 95% CI 0.4314, 0.9091), instrumental vaginal delivery, cesarean delivery (p = 0.0072, RR 0.5745, 95% CI 0.3696, 0.8929), shoulder dystocia, PPH, macrosomia, neonatal asphyxia, admission to NICU were reported more in Group II women (waist circumference>80 cms) as compared to Group I (waist circumference<80 cms).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is the fifth leading cause of death worldwide. (Gupta et al, 2015) did a study in the United States during the time of urban age and discovered that 24.5 percent of women aged 20-44 years are overweight and 23 percent are obese. Excessive eating of red meat, whole grains, desserts, sweet taste, and potatoes, according to research conducted by (Okube & Omandi, 2019), may contribute to long-term weight gain.…”
Section: Introductionmentioning
confidence: 99%